Transcriptome analysis identification of A-to-I RNA editing in granulosa cells associated with PCOS - Kong, Fan-Sheng; Lu, Zijing; Zhou, Yuan; Lu, Yinghua; Ren, Chun-Yan; Jia, Ruofan; Zeng, Beilei; Huang, Panwang; Wang, Jihong; Ma, Yaping; Chen, Jian-Huan (Frontiers in Endocrinology, 2023)
Background Polycystic ovary syndrome (PCOS) is a complex, multifactor disorder in women of reproductive age worldwide. Although RNA editing may contribute to a variety of diseases, its role in PCOS remains unclear. Methods A discovery RNA-Seq dataset was obtained from the NCBI Gene Expression Omnibus database of granulosa cells from women with PCOS and women without PCOS (controls). A validation RNA-Seq dataset downloaded from the European Nucleotide Archive Databank was used to validate differential editing. Transcriptome-wide investigation was conducted to analyze adenosine-to-inosine (A-to-I) RNA editing in PCOS and control samples. Results A total of 17,395 high-confidence A-to-I RNA editing sites were identified in 3,644 genes in all GC samples. As for differential RNA editing, there were 545 differential RNA editing (DRE) sites in 259 genes with Nucleoporin 43 (NUP43), Retinoblastoma Binding Protein 4 (RBBP4), and leckstrin homology-like domain family A member 1 (PHLDA) showing the most significant three 3′-untranslated region (3′UTR) editing. Furthermore, we identified 20 DRE sites that demonstrated a significant correlation between editing levels and gene expression levels. Notably, MIR193b-365a Host Gene (MIR193BHG) and Hook Microtubule Tethering Protein 3 (HOOK3) exhibited significant differential expression between PCOS and controls. Functional enrichment analysis showed that these 259 differentially edited genes were mainly related to apoptosis and necroptosis pathways. RNA binding protein (RBP) analysis revealed that RNA Binding Motif Protein 45 (RBM45) was predicted as the most frequent RBP binding with RNA editing sites. Additionally, we observed a correlation between editing levels of differential editing sites and the expression level of the RNA editing enzyme Adenosine Deaminase RNA Specific B1 (ADARB1). Moreover, the existence of 55 common differentially edited genes and nine differential editing sites were confirmed in the validation dataset. Conclusion Our current study highlighted the potential role of RNA editing in the pathophysiology of PCOS as an epigenetic process. These findings could provide valuable insights into the development of more targeted and effective treatment options for PCOS.